1984
DOI: 10.2307/1129974
|View full text |Cite
|
Sign up to set email alerts
|

Leave-Takings and Reunions of Infants, Toddlers, Preschoolers, and Their Parents

Abstract: The leave-taking and reunion behaviors of infants, toddlers, preschoolers, and their parents were observed as the children were "dropped off" and "picked up" at their nursery school each day. On arrival at their classroom, infants and toddlers related primarily to their parents, whereas preschoolers related to their teachers. Girls more frequently engaged in interaction with their teachers, and boys more frequently approached the children's play activities. Distress behaviors during the parents' departures wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1

Year Published

1988
1988
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 0 publications
1
16
1
Order By: Relevance
“…Several studies have shown that parents even tend to preserve their typical paternal or maternal style of play (physical vs. pretend), independently of social and family conditions (Field, 1978;Field, Gewirtz, Cohen, Garcia, Greenberg, & Collins, 1984;Hossain & Roopnarine, 1994;Stuckey, McGhee, & Bell, 1982). More studies should be conducted, on the one hand to verify this hypothesis, and on the other to verify if characteristics regarding the parents' personal history may influence RTP frequency.…”
Section: Determinants Of Parent-child Rtp Frequencymentioning
confidence: 99%
“…Several studies have shown that parents even tend to preserve their typical paternal or maternal style of play (physical vs. pretend), independently of social and family conditions (Field, 1978;Field, Gewirtz, Cohen, Garcia, Greenberg, & Collins, 1984;Hossain & Roopnarine, 1994;Stuckey, McGhee, & Bell, 1982). More studies should be conducted, on the one hand to verify this hypothesis, and on the other to verify if characteristics regarding the parents' personal history may influence RTP frequency.…”
Section: Determinants Of Parent-child Rtp Frequencymentioning
confidence: 99%
“…Fathers who are more involved in caregiving and mothers who have paid employment do not alter their typical paternal or maternal styles of play [Field, 1978;Stuckey, McGhee & Bell, 1982]. Field et al [1984] have shown that while working mothers play more with their infants than fathers, they tend to engage in face-to-face play. Hossain and Roopnarine [1994] have shown that African-American fathers spend more time playing with than caring for their children despite an equitable division of caregiving responsibilities.…”
Section: The Father-child Activation Relationshipmentioning
confidence: 99%
“…Only a few studies have addressed this topic. In one of the earliest of these, Field et al (1984) observed the leave-taking and reunion behaviours of 3-to 69-month-old children and their parents at a nursery school. The differences in the children's and parent's behaviours were found to be dependent on the child's age, gender and duration of time in school as well as the parent's gender.…”
Section: Daily Arrivalsmentioning
confidence: 99%